The effect of transition gradient in thermochromic glazing systems - Michael Warwick (Energy and Buildings, 2014)
Thermochromic glazing theoretically has the potential to lead to a large reduction in energy demand in modern buildings by allowing the transmission of visible light for day lighting whilst reducing unwanted solar gain during the cooling season, but allowing useful solar gain in the heating season. In this study building simulation is used to examine the effect of the thermochromic transition gradient on the energy demand characteristics of a model system in a variety of climates. The results are also compared against current industry standard glazing products. The results suggest that in a warm climate with a low transition temperature and sharp hysteresis gradient energy demand can be reduced by up to 51% compared to a conventional double glazing approach.